2004
DOI: 10.1002/pd.942
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus (CMV) glycoprotein B genotype and CMV DNA load in the amniotic fluid of infected fetuses

Abstract: Neither gB genotype nor CMV DNA load in AF correlate with the severity of CMV congenital infection and these markers are unlikely to prove useful for the management of congenital infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 24 publications
9
51
0
6
Order By: Relevance
“…It is therefore not relevant to test for UL144 genotypes in this context. Other HCMV polymorphisms, such as glycoprotein B genotypes, have been evaluated in congenital infection and also proved to be disappointing (2,3,5,13,15,21). Moreover, it was recently demonstrated that the inter-and intragenic variability of HCMV clinical isolates leads to an infinite number of genetic combinations, probably explaining the failure to use sequence information to predict disease outcome (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore not relevant to test for UL144 genotypes in this context. Other HCMV polymorphisms, such as glycoprotein B genotypes, have been evaluated in congenital infection and also proved to be disappointing (2,3,5,13,15,21). Moreover, it was recently demonstrated that the inter-and intragenic variability of HCMV clinical isolates leads to an infinite number of genetic combinations, probably explaining the failure to use sequence information to predict disease outcome (16).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonographic reports, outcome, and/or postmortem examination reports were collected. Some of these cases have also been described elsewhere (15). We classified the fetuses into two groups.…”
Section: Patients and Samples Between February 2001 And May 2002mentioning
confidence: 99%
“…In addition, some of the methods previously described are not easily applied to high-throughput monitoring. Based on Chou's classification of gB genotypes, several methods of genotyping CMV gB were adapted, including restriction fragment analysis (RFA) of PCR products (16,20,34), conventional multiple nested PCR (4,28,38), and direct DNA sequencing (24). All of these methods either lack sensitivity or are labor intensive and/or nonquantifiable.…”
mentioning
confidence: 99%
“…Although CMV infection is diagnosed when detected in amniotic fluid by PCR, there is no relationship between the CMV gene dosage in the amniotic fluid and neonatal prognosis [18]. The CMV-DNA level in umbilical cord venous blood was used to diagnose the presence of the viral infection; however, it did not appear to be a suitable indicator of therapeutic effect.…”
Section: Extent Of Fetal CMV Invasionmentioning
confidence: 99%